USE OF QR CODE AS A FACILITATING INSTRUMENT IN TEACHING MITOSIS: A DIDACTIC SEQUENCE - Silva, Luciana Rodrigues Oliveira da (2024)
In the teaching of Biology, practical and innovative activities are becoming increasingly common in classrooms. These approaches are adopted by teachers with the aim of fostering new skills and competencies in students, as well as promoting a more dynamic and meaningful teaching and learning process. The purpose of this study is to describe a didactic sequence developed through a practical activity and to evaluate the participation and involvement of students. The research adopts a qualitative approach and is inserted in the context of the training of future educators, with Basic Education as an area of intervention. The results obtained reinforce the need to update methodologies and invest in the development of knowledge that can positively benefit the lives of students.